1985
DOI: 10.1017/s0264180100001879
|View full text |Cite
|
Sign up to set email alerts
|

Handedness, language dominance and aphasia: a genetic model

Abstract: for their extensive discussion of the ideas contained in this paper. I also wish to thank the National Children's Bureau, and in particular Mr K. Fogelman who gave me permission to re-analyse the data obtained by the National Child Development Study, and the Survey Archive of the Social Science Research Council, and in particular Mr E. Roughley who provided those data. Drs Mascie-Taylor, Chaurasia and Goswami kindly gave me permission to quote from their unpublished data, for which I am very grateful. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
300
4
10

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(323 citation statements)
references
References 104 publications
9
300
4
10
Order By: Relevance
“…Dichotic listening should not be regarded as directly diagnostic of cerebral speech asymmetry but there is a positive relationship in typical cases [9]. In RR pairs, Springer and Searleman found concordance for typical right Geschwind et al [17] referred to two other theories that adopt a chance postulate to account for left-handedness, those of McManus [22] and Klar [18]. These theories resemble the RS theory in proposing a typical directional bias and chance in the absence of that bias.…”
Section: Rs Genotypes By Handedness In Mz and Dz Twinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichotic listening should not be regarded as directly diagnostic of cerebral speech asymmetry but there is a positive relationship in typical cases [9]. In RR pairs, Springer and Searleman found concordance for typical right Geschwind et al [17] referred to two other theories that adopt a chance postulate to account for left-handedness, those of McManus [22] and Klar [18]. These theories resemble the RS theory in proposing a typical directional bias and chance in the absence of that bias.…”
Section: Rs Genotypes By Handedness In Mz and Dz Twinsmentioning
confidence: 99%
“…McManus [22] proposed that the 'true' incidence of left-handedness is 7.75 percent and that other values in the literature are in error. In fitting the theory to observations, genotypes are re-assigned to phenotypes to allow for supposed errors in the data, so making the model unfalsifiable over the typical range of incidences of left-handedness.…”
Section: Rs Genotypes By Handedness In Mz and Dz Twinsmentioning
confidence: 99%
“…The pervasiveness of human right-handedness has led to numerous debates about the mechanisms involved in the expression of hand preference (B. Hopkins & Ronnqvist, 1998). Both genetic models (Annett, 1985;Corballis, 1997;Laland, Kumm, Van Horn, & Feldman, 1995;McManus, 1985;Yeo & Gangestad, 1993) and environmental models (Collins, 1985;Provins, 1997) have been proposed to explain the origin of human hand preference. The principal data in support of a genetic basis for hand preference are that it runs in families (Curt, De Agostini, Maccario, & Dellatolas, 1995;Laland et al, 1995;McGee & Cozad, 1980;McManus & Bryden, 1992) and that offspring typically exhibit patterns of hand preference more similar to their biological parents compared with offspring who have been adopted or raised by stepparents (Carter-Saltzman, 1980;Hicks & Kinsbourne, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Such a model has been developed by Laland et al [31,32]. Following a notation by McManus [35,36], they assume that the probability of becoming left-or right-handed is influenced by two additive alleles D (Dextral) and C (Change) on a single locus. The genetic probability of being right-handed for an individual with two D alleles is than calculated by adding p, a factor that represents the dextralising effect of this genotype, to 0.5, the chance probability of being right-handed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the development of behavioural asymmetries in birds, it is widely assumed that environmental factors do not play a large role in determining individual handedness and a number of different single-gene models have been proposed to explain the distribution of left-and right-handedness [1,9,27,28,35,36]. Recently it has been reported that the gene LRRTM1 on chromosome 2p12 is the first identified genetic influence on human handedness [17], a claim that is heavily discussed since it has been publicised [10,16,37].…”
Section: Introductionmentioning
confidence: 99%